Rationale and design of the Investigator-Steered Project on intravascular Renal Denervation for Management of Drug-Resistant Hypertension (INSPiRED) trial. (June 2014) - Jin, Yu; Jacobs, Lotte; Baelen, Marie; Thijs, Lutgarde; Renkin, Jean; Hammer, Frank; Kefer, Joelle; Petit, Thibault; Verhamme, Peter; Janssens, Stefan; Sinnaeve, Peter; Lengelé, Jean-Philippe; et al.
Abstract The SYMPLICITY studies showed that renal denervation (RDN) is feasible as novel treatment for resistant hypertension. However, RDN is a costly and invasive procedure, the long-term efficacy and safety of which has not yet been proven. Therefore, we designed the INSPiRED trial to compare the blood pressure lowering efficacy and safety of RDN vs usual medical therapy. INSPiRED is a randomized controlled trial enrolling 240 treatment-resistant hypertensive patients at 16 expert hypertension centres in Belgium. Eligible patients, aged 20–69 years old, have a 24-h ambulatory blood pressure of 130 mmHg systolic or 80 mmHg diastolic or more, while taking at least three antihypertensive drugs. They are randomized to RDN (EnligHTNTM, SJM system) plus usual care (intervention group) or usual care alone (control group) in a ratio of 1:1. The primary endpoints for efficacy and safety, measured after 6 months, are the baseline-adjusted between-group differences in 24h systolic blood pressure and in glomerular filtration rate as estimated by the Chronic Kidney Disease Epidemiology Collaboration equation. Follow-up will continue up to 36 months after randomization. INSPiRED is powered to demonstrate a 10-mmHg difference in systolic blood pressure between randomized groups with a two-sided p-value of 0.01 and 90% power. It will generate long-term efficacy and safety data, identify the subset of treatment-resistant hypertensive patients responsive to RDN, provide information on cost-effectiveness, and by doing so INSPiRED will inform guideline committees and health policy makers. Trial registration: ClinicalTrials.gov Identifier: NCT 01505010.